1986
DOI: 10.1073/pnas.83.23.8819
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of rat bone sialoprotein (osteopontin) cDNA reveals an Arg-Gly-Asp cell-binding sequence.

Abstract: The primary structure of a bone-specific sialoprotein was deduced from cloned cDNA. One of the cDNA clones isolated from a rat osteosarcoma (ROS 17/2.8) phage Xgtll library had a 1473-base-pair-long insert that encoded a protein with 317 amino acid residues. This cDNA done appears to represent the complete coding region of sialoprotein mRNA, including a putative AUG initiation codon and a signal peptide sequence. The amino acid sequence deduced from the cDNA contains several Ser-Xaa-Glu sequences, possibly rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
615
0
18

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 997 publications
(644 citation statements)
references
References 40 publications
11
615
0
18
Order By: Relevance
“…OPN is a phosphoglycoprotein originally isolated from bone extracellular matrix [29]. It is synthesized by a variety of immune and nonimmune cells including macrophages, lymphocytes, fibroblasts, osteoclasts, epithelial cells, endothelial cells, and smooth muscle cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…OPN is a phosphoglycoprotein originally isolated from bone extracellular matrix [29]. It is synthesized by a variety of immune and nonimmune cells including macrophages, lymphocytes, fibroblasts, osteoclasts, epithelial cells, endothelial cells, and smooth muscle cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that FGD1 is required for effective transport of cargo proteins from the Golgi complex to the plasma membrane in general, whereas in osteoblasts it regulates the secretion of PC-I, osteocalcin, osteonectin, and osteopontin. All of these proteins have fundamental roles in the generation of mineralized extracellular matrix during bone development (Lian et al, 1978;Termine et al, 1981;Oldberg et al, 1986;Leblond, 1989), and therefore their aberrant transport through a lack of FGD1 are likely to contribute to the FGDY manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…All of these proteins are soluble (i.e., reside in the lumen of secretory compartments), and therefore they have a topology different from that of VSVG (which is a transmembrane protein). Moreover, they are of different sizes, being either relatively small (osteocalcin, osteonectin, and ostopontin; Lian et al, 1978;Termine et al, 1981;Oldberg et al, 1986) or forming large supramolecular aggregates within early compartments of the secretory pathway (PC-I; Leblond, 1989). All of these proteins have fundamental roles in bone morphogenesis.…”
Section: Fgd1 Is Required For Transport Of Bone Proteins In Osteoblastsmentioning
confidence: 99%
“…It is a sialic acid-rich phosphorylated glycoprotein originally isolated from the bone. The opn gene contains a Gly-Arg-Gly-Asp-Ser (GRGDS) -encoding motif that promotes cell attachment via avb3 integrin (Oldberg et al, 1986) and CD44 (Weber et al, 1996). Opn has been suggested to play important roles in the process of neoplastic metastasis (Brown et al, 1994;Oates et al, 1996) by enhancement of cell attachment through Opn receptors.…”
Section: Introductionmentioning
confidence: 99%